Pengaruh Audit Tenure Dan Audit Fee Terhadap Kualitas Audit dengan Komite Audit Sebagai Pemoderasi - Muhammad Bad'rul Choirul Ullum; Yuha Nadhirah Qintharah (JRAK: Journal of Accounting Research and Computerized Accounting, 2025)
The purpose of this study is to examine the effect of audit tenure and audit fee on audit quality with audit committee as moderating variable. The population used in this study are transportation and logistic companies listed on the Indonesia Stock Exchange (IDX) for the period 2021-2023. The sampling was done by using purposive sampling method and total sample in this study was 54 samples. Proxy measurements for audit tenure is calculating the years in which the same auditor has collaborated with clients, audit fee is measured by logaritma natural of professional fees, audit committee is measured by comparing the number of audit committees with the number of commissioners, while audit quality is measured by dummy variable. The moderated regression analysis with SPSS 30 software was used to analyze data. The results showed that audit tenure has no effect on audit quality, audit fee is positive significant affecting on audit quality, while audit committee is unable to moderate the effect of audit tenure and audit fee on audit quality.